2021
DOI: 10.31234/osf.io/rz6qn
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Children infer the behavioral contexts of unfamiliar foreign songs

Abstract: Humans readily make inferences about the behavioral context of the music they hear. These inferences tend to be accurate, even if the songs are in foreign languages or unfamiliar musical idioms: upon hearing a Blackfoot lullaby, a Korean listener with no experience of Blackfoot music, language, or broader culture is far more likely to judge the music’s function as “to soothe a baby” than as “for dancing”. Are such inferences shaped by musical exposure or does the human mind naturally detect certain links betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…Despite its youth, the study of the cultural evolution of music has resulted in some important insights. For example, research on traditional and folk music have revealed that scales around the world have a tendency to converge towards similar patterns (McBride and Tlusty, 2019;Brown and Jordania, 2013;Kuroyanagi et al, 2019), musical variation is correlated with social complexity (Lomax, 1968;Wood et al, 2021) and sometimes population history (Brown et al, 2014; but see Matsumae et al, 2021), and that certain styles of music are reliably associated with particular behavioral contexts across cultures (Mehr et al, 2019) according to their acoustic features (Mehr et al, 2018;Hilton et al, 2021). Studies of classical music have found that melodic intervals are associated with particular historical periods (Rodriguez Zivic et al, 2013;Weiß et al, 2019;Harasim et al, 2021), and that tonal complexity and harmonic richness have increased over time ( Weiß et al, 2019;Serra-Peralta et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its youth, the study of the cultural evolution of music has resulted in some important insights. For example, research on traditional and folk music have revealed that scales around the world have a tendency to converge towards similar patterns (McBride and Tlusty, 2019;Brown and Jordania, 2013;Kuroyanagi et al, 2019), musical variation is correlated with social complexity (Lomax, 1968;Wood et al, 2021) and sometimes population history (Brown et al, 2014; but see Matsumae et al, 2021), and that certain styles of music are reliably associated with particular behavioral contexts across cultures (Mehr et al, 2019) according to their acoustic features (Mehr et al, 2018;Hilton et al, 2021). Studies of classical music have found that melodic intervals are associated with particular historical periods (Rodriguez Zivic et al, 2013;Weiß et al, 2019;Harasim et al, 2021), and that tonal complexity and harmonic richness have increased over time ( Weiß et al, 2019;Serra-Peralta et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…For example, music is associated with particular behavioral contexts across societies (e.g. ritual, dance, infancy), and the primary context in which a song is used is associated with certain acoustic features (Mehr et al, 2019) and reliably recognized by both adults (Mehr et al, 2018) and children (Hilton et al, 2021). Variation in musical styles across societies also appears to be robustly correlated with social complexity (Lomax, 1968;Wood et al, 2021).…”
Section: Traditional and Folk Musicmentioning
confidence: 99%
“…We then examined the precise relations between acoustic features and the experiment-wide proportions of infant-directedness ratings for each vocalization, in a similar approach to prior research 73 . The proportions are a more strenuous target to predict than a binary classification (as in the first two LASSO models) in that they form a continuous measure of infant-directedness per the ears of the naïve listeners.…”
Section: Human Intuitions Of Infant-directedness Are Modulated By Vocalization Acousticsmentioning
confidence: 99%
“…Citizen-science methods are limited, however, by the need to factor in participants' interests and incentives; the need to avoid factors that might dissuade participation (e.g., clunky user interfaces, boring time-consuming tasks), which can require graphic design and web development talent for "gamification" (e.g., Cooper et al, 2010); the risks of recruiting a biased population subset (i.e., those with internet access; Lourenco & Tasimi, 2020); and the trade-offs between densely sampling stimuli across-versus within-participants, given the typically short duration of citizen-science experiments. Indeed, while our efforts to recruit children at scale online via citizen science show promising results (Hilton, Crowley de-Thierry, Yan, Martin, & Mehr, 2021), rare or hard-to-study populations may be difficult to recruit en masse (cf. Lookit, a platform for online research in infants; Scott & Schulz, 2017).…”
Section: Conflict Of Interest Nonementioning
confidence: 99%